AzaHx, a novel fluorescent, DNA minor groove and G·C recognition element: Synthesis and DNA binding properties of a p-anisyl-4-aza-benzimidazole-pyrrole-imidazole (azaHx-PI) polyamide. Issue 17 (1st September 2015) - Satam, Vijay; Babu, Balaji; Patil, Pravin; Brien, Kimberly A.; Olson, Kevin; Savagian, Mia; Lee, Megan; Mepham, Andrew; Jobe, Laura Beth; Bingham, John P.; Pett, Luke; Wang, Shuo; et al.
Graphical abstract